Big Five personality predict epilepsy diagnosis in 7 years - Kang, Weixi (Frontiers in Neurology, 2023)
Objective Recently, there is growing interest in investigating how personality traits could predict a subsequent diagnosis of various diseases. Regarding epilepsy, there is only preliminary evidence based on cross-sectional studies linking personality traits to epilepsy, hence, emphasizing the need for longitudinal studies. The aim of the current study is to assess if the Big Five personality traits can predict the risk of an epilepsy diagnosis. Methods The current study analyzed data from 17,789 participants who participated in “Understanding Society: the UK Household Longitudinal Study (UKHLS)” at Wave 3 (collected between 2011 and 2012) and Wave 10 (collected between 2018 and 2019). The mean age was 47.01 (SD=16.31) years and were 42.62% male. Two binary logistic regressions were used by including age, monthly income, highest educational qualification, legal marital status, residence, and personality traits scores at Wave 3 as predictors for a clinical diagnosis of epilepsy at Wave 10 for males and females respectively. Results There were 175 participants (0.98%) with epilepsy and 17,614 participants (99.02%) without epilepsy at Wave 10. Results of the binary regression analyses revealed that Neuroticism is positively related to the risk of an epilepsy diagnosis in males (OR=1.32, p=0.04, 95% CI [1.01, 1.71]) but not in females 7 years after Wave 3 at Wave 10. Conclusion These findings suggest that personality traits might enhance our understanding of psychophysiological associations in epilepsy. Neuroticism might be a relevant factor that should be taken into account in epilepsy education and treatment. Moreover, sex differences must be taken into account.